The Patient Experience With Shared Decision Making: A Qualitative Descriptive Study. Issue 6 (November 2015) - Truglio-Londrigan, Marie
Abstract : Shared decision making is a process characterized by a partnership between a nurse and a patient. The existence of a relationship does not ensure shared decision making. Little is known about what nurses need to know and do for this experience to take place. A qualitative descriptive study was implemented using Coalizzi's method. Semistructured interviews were held with patients, and 3 themes were uncovered. The findings suggest that a nurse's conduct aimed at drawing patients in and inviting them to participate in a conversation leads toward shared decisions. Infusion nurses may find this information useful as they engage their patients in shared decisions.